Analisis Pemberdayaan Perempuan Berbasis Umkm Dalam Meningkatkan Kewirausahaan Keluarga Di Kecamatan Benowo, Surabaya - Nuraini Kusuma Andriyani; Miskan; Wulandari, Sutiowati; Tri Putra, Bayu (Jurnal ilmiah Manajemen Publik dan Kebijakan Sosial, 2023)
Entrepreneurial skills need to be applied to every individual because it requires everyone to have non-academic abilities and skills that are useful for creating quality human resources. This research aims to provide a concrete study regarding the empowerment of UMKM women in improving their entrepreneurial abilities, based on the results of field interviews. Women's empowerment carried out in Benowo district aims to create opportunities for the establishment of effective UMKM-based businesses. This research methodology uses explanatory qualitative research based on UMKMs to strengthen family entrepreneurship with the aim of empowering the community, especially women. The respondents were the Benowo District government, PKK cadres and UMK actors, especially women. And the focus of this research is UMKM-based women's empowerment in increasing family entrepreneurship in Benowo District and the results obtained in this research are that women's empowerment in Benowo District has been implemented well, as evidenced by the many programs that support women's empowerment such as UMKM moving up to class, product photography training, training in managing business permits to applying for initial capital for those who want to start a business, namely by collaborating with Bank Jatim, BRI and Regional Banks. From the results that have been obtained, the conclusion of this research is that there is a program for upgrading UMKM which is a superior program to increase women's empowerment. However, the suggestion from researchers is that there needs to be a more intense approach to the community, especially UMKM actors who are still unable and not willing to join because several factor, the Benowo District Government can take an approach by visiting several sub-districts throughout Benowo District. The targeted output of this research is to create profit-oriented entrepreneurial skills. Apart from that, this research is targeted to be able to produce the proceedings of a national seminar so that it will be widely explored in the community regarding the analysis of UMKM-based women's empowerment in increasing family entrepreneurship, and will also be presented in journal form to add to the line of knowledge about women's empowerment.